Isolation and Identification of Lactic Acid Bacteria in Sinjai Typical Drinks (MINAS) - Miladiarsi, Miladiarsi Mila; Wahdaniar, Wahdaniar (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2024)
A fermented drink produced locally in the Sinjai area that is well known in the local community as well as widely is Minas. Minas, which means a typical Sinjai drink, used to be known as Irex. However, over time this drink was replaced with the name Minas because it was only produced in Sinjai City and used as a typical Sinjai drink has properties and benefits to increase body stamina due to fatigue after doing daily activities or work. Minas are made from cassava tapai, young coconut, eggs, coconut water, sugar water, honey, and milk and can be added with other fruits such as durian. Curved tape is a type of food produced from the fermentation process of substrates or carbohydrate foodstuffs using yeast yeast which belongs to the group of lactic acid bacteria. To determine the type of lactic acid bacteria that play a role in the fermentation process of minas drinks by isolating and identifying morphology using the gram staining method, biochemical tests using catalase tests, gas production and carbohydrate fermentation tests. Furthermore, molecular identification uses 16S RNA. The DNA sequencing results were analyzed with MEGA 6 software with the BLASTn algorithm at NCBI. Based on the results of the identification of lactic acid bacteria, homologous nucleotides were detected with the bacteria Bacillus subtilis, Bacillus and Streptococcus sp which are a group of lactic acid bacteria that are able to ferment carbohydrates to produce lactic acid.